Lepenism and Marinism: Variations and Invariants of Populist Identity Discourse - Alberdi Urquizu, Carmen (Populismo y propaganda: entre el presente y el pasado, 2020)
The « Lepenism », the ideological-discursive system of the French Front national, seems to have generated in recent years a softened version of itself, the so-called « Marinism », aimed to ensure the normalisation of the party and the support of voters from other camps. However, the same nationalist and identity populism emerges underneath this policed surface, namely throughout the manipulation of the unspoken meanings.